An Explanation and Some Experiments for Solving the Neutron Lifetime Puzzle Via Non Standard Neutrino Interactions - Adams, Barry D.O. (Current Research Progress in Physical Science Vol. 7, 2025)
The neutron lifetime puzzle, characterized by a discrepancy between beam (887 seconds) and magnetic bottle (879 seconds) measurements, remains unsolved. This manuscript proposes an innovative explanation involving non-standard neutrino interactions and the inverse quantum Zeno effect. These interactions could reduce the neutron lifetime in magnetic bottle experiments to the observed value. To test this hypothesis, we suggest some experiments using isotopically varied materials and ultra-cold neutron sources. If validated, this work could deepen our understanding of fundamental forces, with significant implications for cosmology, dark matter, and particle physics.